2023
DOI: 10.1039/d2fo02026b
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside CK improves skeletal muscle insulin resistance by activating DRP1/PINK1-mediated mitophagy

Abstract: Skeletal muscle insulin resistance is the main cause of type 2 diabetes, and mitochondria play a key role. Ginsenoside CK is main active compound of ginseng with a variety of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…55 Fan et al found that ginsenoside CK improved skeletal muscle insulin resistance by activating Pink1/Parkin-induced mitophagy and restoring Pink1/Parkin-enhanced autophagy flow. 56 In our previous study, we determined that linolenic acid ameliorated mitochondrial function in C. elegans with sarcopenia by inducing Pink1/Parkin-mediated mitochondrial autophagy. 57 In this study, we report that GA, EA, and NA promoted mitophagy by mediating the LC3-I to LC3-II transition, elevating the expression of ATG5 and decreasing the expression of p62 via enhancement of the Pink1/Parkin pathway in oxaliplatin-induced RSC96 cells.…”
Section: Discussionmentioning
confidence: 98%
“…55 Fan et al found that ginsenoside CK improved skeletal muscle insulin resistance by activating Pink1/Parkin-induced mitophagy and restoring Pink1/Parkin-enhanced autophagy flow. 56 In our previous study, we determined that linolenic acid ameliorated mitochondrial function in C. elegans with sarcopenia by inducing Pink1/Parkin-mediated mitochondrial autophagy. 57 In this study, we report that GA, EA, and NA promoted mitophagy by mediating the LC3-I to LC3-II transition, elevating the expression of ATG5 and decreasing the expression of p62 via enhancement of the Pink1/Parkin pathway in oxaliplatin-induced RSC96 cells.…”
Section: Discussionmentioning
confidence: 98%
“…96 Additionally, ginsenoside compound K (CK), a primary active compound in ginseng, increases insulin sensitivity and alleviates IR by stimulating mitophagy in the skeletal muscle of db/db mice. 97 Moreover, the promotion of autophagy via the SIRT1forkhead box transcription factor O1 signalling pathway has been shown to alleviate abnormal lipid metabolism and attenuate IR in the skeletal muscle of Zucker diabetic fatty rats. 98 These findings underscore the significance of a properly regulated autophagic activity in enhancing insulin sensitivity and balancing glucolipid metabolism within muscle tissues.…”
Section: Skeletal Musclementioning
confidence: 99%
“…Extensive research has shown that mitophagy can improve MQC by increasing ROS production and inhibiting the inflammatory response in adipocytes, thereby inhibiting hepatic IR and steatosis 8,43 . A recent study found that ginsenoside CK could activate mitophagy in skeletal muscle through the DRP1/PINK1 pathway to maintain MQC, thereby reducing IR in diabetic mice 44 . In brief, mitophagy can exert its inhibitory effects in IR by maintaining MQC, promoting oxidative stress and inhibiting inflammatory responses, but there are still few studies on the related molecular mechanisms, and a large number of experiments are needed to verify them.…”
Section: Mitophagy In Msmentioning
confidence: 99%